Analisis Pengaruh Penambahan Serbuk Pelepah Kelapa Sawit Pada Komposit Berbasis Semen Untuk Peredam Panas - Ilham Ary Wahyudie; Sulistiana Rachmadini; Muhammad Riva’i (Infotekmesin, 2024)
In palm oil plantations, the fruit and empty bunches are usually used, while waste such as oil palm fronds (PKS) is often disregarded. However, pruned PKS can be utilized in the production of environmentally friendly building materials that serve as heat insulators. PKS waste can be used as an additional aggregate to create eco-friendly bricks by grinding it into powder and mixing it with sand and cement. A multilevel factorial experimental design was used to vary the percentage of PKS powder and the sand-cement ratio. The analysis results showed that the addition of PKS powder significantly improved heat insulation, resulting in a temperature reduction of up to 19.54°C in a mixture containing 20% PKS powder and a sand-cement ratio of 2:1. The percentage of PKS powder also significantly influenced heat insulation capacity, with an F-value of 7.0 compared to an F-table value of 3.88. Additionally, the interaction between the sand-cement ratio and the percentage of PKS powder had an F-value of 19.56, indicating a solid impact on heat insulation capability.